THE EFFORTS FOR EARLY DETECTION OF BHABINKAMTIBMAS TO PREVENT RADICALISM IN THE JURISDICTION OF POLRES TEGAL CITY: THE EARLY DETECTION OF BHABINKAMTIBMAS - mochammad nurfauzan muttaqien (Police Studies Review, 2022)
ABSTRACT EFFORTS FOR EARLY DETECTION OF BHABINKAMTIBMAS TO PREVENT RADICALISM IN THE JURISDICTION OF POLRES TEGAL CITY Mochammad Nurfauzan Muttaqien, 18,028, mnurfauzanm@gmail.com Bhabinkamtibmas is the spearhead of the National Police, because it is a member of the National Police who is directly in the community. Bhabinkamtibmas itself aims to carry out the development of security and public order, one of which is also to prevent the spread of radicalism that can cause disturbances to the security and social order, so that Bhabinkamtibmas is given additional duties in Perkap No. 7 of 2021 to carry out early detection of kamtibmas disturbances. The research location in this final project is the Tegal City Police Station. The problem taken is how the competence of Bhabinkamtibmas is and how to implement early detection efforts to prevent radicalism in the jurisdiction of the Tegal City Police. This final project is a qualitative research, using the field research method. This study uses several concepts and theories such as management theory, competency theory, and the concept of radicalism, as well as the concept of Bhabinkamtibmas. The results of the study indicate that the implementation of the activities is not in accordance with what it should be, and there are still constraints in the competencies possessed by Bhabinkamtibmas such as not being given a training session. Therefore, there is a need to solve this problem.